Law enforcement and auditors' roles, responses, and complicated relationships in accounting fraud? - Djuharni, Darti; Nursaid, Nursaid; Sonhaji, Sonhaji (CV. Bimbingan Belajar Assyfa, 2023)
Accounting fraud is a form of financial report manipulation that has a serious impact on various economic and social aspects. Apart from being financially detrimental, this fraud also affects employees, industry, and society. This research aims to understand the role of auditors and law enforcement in preventing and handling accounting fraud, with a focus on the complex relationship between these two parties. Using a mixed methods research synthesis, we analyzed journal articles from 2014 to 2024 that covered this topic. Data was collected from various sources such as SINTA, Semantic Scholar, and Google Scholar. The research results show that there are differences in terminology and concepts of fraud among existing studies, as well as fraud analyses that are often superficial. We suggest the need for more in-depth case studies of the interactions between law enforcement and auditors. These findings underscore the importance of collaboration between academics, politicians, and practitioners to reduce the economic and social impact of accounting fraud.